What’s in a Scriven Number? - Abhik R. Roy; Kristin A. Hobson; Chris L. S. Coryn (Journal of MultiDisciplinary Evaluation)
Background: Other than Leonhard Euler, one of the greatest physicists and mathematicians ever to have lived and dubbed “…c'est notre maître à tous” or “…the master of us all” by the French mathematician and astronomer Pierre-Simon Laplace, Paul Erdös was a mathematician who published more papers in mathematics than anyone else (Hoffman, 1998). Because of this feat, friends and colleagues created what has been known as an Erdös number. An Erdös number describes a person’s degree of separation from Erdös through collaborations directly with him or with others who have collaborated with him.